The Role Of Good Governance In Mediating Literacy, Income And Cash Waqf Decisions - Qomariah, Qomariah; Setiyowati, Supami Wahyu; Irianto, Mochamad Fariz (LPPM ISNJ Bengkalis, 2024)
This research aims to analyze the influence of literacy, income and good governance on cash waqf decisions and examine the role of good governance as a mediating variable in this relationship. The research method uses a quantitative approach with primary data by distributing questionnaires online and offline to the waqifs. This research's population is the General Ahmad Yani Mosque, Malang City congregation. A total of 76 samples were collected using a purposive sampling technique. The research model uses Partial Least Square structural equations with the help of SmartPLS software version 4.1.0. by testing the outer model, inner model, and hypothesis. The research results reveal a positive and significant influence between literacy, income, and good governance when giving cash waqf. Good governance can mediate the influence of literacy and income on giving cash waqf. Cash waqf is not only influenced by literacy and income factors, but the implementation of institutional solid good governance can strengthen the trust of wakifs, thereby increasing cash waqf revenues. This research can complement previous theories and become a reference for further research. This research can be a reference for cash waqf managers in increasing the number of waqifs and implementing good governance.